Spinal motoneuron excitability is homeostatically-regulated through β-adrenergic neuromodulation in wild-type and presymptomatic SOD1 mice - Antonucci, Stefano; Caron, Guillaume; Dikwella, Natalie; Krishnamurty, Sruthi Sankari; Harster, Anthony; Zarrin, Hina; Tahanis, Aboud; Heuvel, Florian Olde; Danner, Simon M; Ludolph, Albert C; Grycz, Kamil; Bączyk, Marcin; et al. (bioRxiv, 2024)
Homeostatic feedback loops are essential to stabilize the activity of neurons and neuronal networks. It has been hypothesized that, in the context of Amyotrophic Lateral Sclerosis (ALS), an excessive gain in feedback loops might hyper- or hypo-excite motoneurons (MNs) and contribute to the pathogenesis. Here, we investigated how the neuromodulation of MN intrinsic properties is homeostatically controlled in presymptomatic adult SOD1(G93A) mice and in the age-matched control WT mice. First, we determined that β2 and β3- adrenergic receptors, which are Gs-coupled receptors and subject to tight and robust feedback loops, are specifically expressed in spinal MNs of both SOD1 and WT mice at P45. We then demonstrated that these receptors elicit a so-far overlooked neuromodulation of the firing and excitability properties of MNs. These electrical properties are homeostatically regulated following receptor engagement, which triggers ion channel transcriptional changes and downregulates those receptors. These homeostatic feedbacks are not dysregulated in presymptomatic SOD1 mice, and they set the MN excitability upon β-adrenergic neuromodulation.